Pamięć o rodzeństwie Scholl w filmach Michaela Verhoevena i Percy'ego Adlona - konteksty i interpretacje - Klejsa, Konrad (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2012)
This paper analyses two German feature films dedicated to the life of Sophie Scholl: The White Rose (Die Wei#e Rose, dir. Michael Verhoeven) and Five Last Days (Fünf letzte Tage, dir. Percy Adlon). They both premiered in 1982 and caused a nationwide debate on the legacy of German anti-Nazi movement. Drawing on German memory culture, which underwent vital changes in the post-1968 period, the author focuses on the dramaturgy of both movies and various differences in treating the material which is “based on facts”. It is argued that Verhoeven’s film obliterates the religious background of the White Rose, while Five Last Days fails to discuss the group’s political agenda. In the conclusion the impact of both movies on the German public is presented (a special attention is given to the prosecutions against war-time criminals who convicted and sentenced the White Rose’s members).